THE RELATIONSHIP BETWEEN INFLATION RATE AND UNEMPLOYMENT RATE IN INDONESIA, 1985-2008 - Selli Nelonda (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
This paper aims to investigate the relationship between inflation rate and unemployment. Tradeoff between inflation and unemployment rate showed a negative correlation between unemployment and wage inflation. Using the OLS method (1985-2008), the estimates indicate that the rate of inflation does not significantly influence the level of unemployment. It can be seen from a positive inflation coefficient value and not significant. Total labor force significantly affect unemployment rates. The unemployment rate last year significant effect on the unemployment rate today. Granger causality test shows that there is no causal relationship between unemployment and inflation.